Study of Non-Allergen Ingredients on Functional Properties and Sensory Acceptability of Jackfruit Burger as Meat Analogue - Mohd Sudin, Hani Zayani; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2023)
The market for plant-based meat substitutes is expanding rapidly, but many of these products contain ingredients that are recognized as high-priority allergens, including milk, eggs, fish, crustacean shellfish, tree nuts, peanuts, wheat, and soy. Many health-conscious consumers worry about their prevalence in processed foods. Thus, the simplest lattice mixture design was utilized in order to optimize jackfruit patties with potato starch, pea starch, and rice flour in order to identify the optimum allergen replacement ingredients. 13 formulations were generated. Physicochemical properties such as color, moisture, pH, and texture along with sensory acceptance were evaluated. The results showed that adding 6.8% rice flour resulted in greater L* and b* values compared to other non-allergen ingredients, whereas adding 6.8% potato starch resulted in higher a* values. Jackfruit patties made with pea starch had an ideal texture. The moisture content of the combination from 2.2% potato starch, 2.2% pea starch, and 2.2% rice flour was the highest than that of other formulations. Sensory evaluation test revealed that jackfruit patties prepared with pea starch were significantly preferred due to a high liking score, with sensory values ranging from 6 to 7 for appearance, taste, texture and overall acceptability. In conclusion, the jackfruit patties formulated with potato starch, pea starch, and rice flour are viable and would provide the industry with a variety of options for selecting the non-allergen ingredients that enable product differentiation and satisfy the rising demand for allergen-free foods.